Lovely Blooms Enterprise / Siti Rokhaida Abdul Khalil... [et al.] - Abdul Khalil, Siti Rohkhaida; Marzuki, Nizza; Shahari, Norasharinaliza; Saad, Noor Hamidah; Hamzah, Rozilawati (2000)
Lovely Blooms is a new kind of business which will provides services in selling, delivery and composing fruits, chocolate, candies and cakes. They look high demand and good feedback from the respondents of the population, it is agreeable to build a company that gives such services. Lovely Blooms will converse the private firm or company for a start such as private hospitals and hotels but it still accept reservation from public. This business started on 1 January 2002. The location of this business was located at Sungai Nibung Kecil, Pulau Pinang.